Effectiveness of steroids and antiviral agents in the treatment of Bell’s palsy - Sialakis, Christos; Frantzana, Aikaterini; Iliadis, Christos; Ouzounakis, Peter; Kourkouta, Lambrini (Medicine and Pharmacy Reports, 2025)
Background. This study aims to investigate the effectiveness of steroids plus antivirals versus steroids alone in the treatment of Bell’s palsy. Due to conflicting results in the existing literature, we conducted this meta-analysis to synthesize the available evidence and extract a more complete conclusion. Methods. We searched electronic databases PubMed, CINAHL, ScienceDirect, MEDLINE, OVID, and Scopus. The last search was performed on March 2024. In this study, 7 randomized controlled trials were included. We used random and fixed effects for sensitivity analysis for each outcome, and we further proceeded to perform a Bayesian meta-analysis using priors and calculate the posterior distribution. Results. Performing frequentist meta-analysis, both the random and fixed effects showed statistical significance, indicating the superiority of the combination treatment. The random log odds ratio was 0.5865 [95% CI: 0.0141 to 1.1589 and the Back-Transform Log Odds Ratio to Odds Ratio was 1.798 [95% CI: 1.014 to 3.186]. The fixed effect log odds ratio was 0.4377 [95%CI: 0.0819 to 0.7934] and the Back-Transform Log Odds Ratio to Odds Ratio was 1.549 [95% CI:1.085 to 2.211]. Neither the rank correlation nor the regression test in both models indicated any funnel plot asymmetry and publication bias. Performing Bayesian meta-analysis, in the posterior distribution the model-averaged log odds ratio was 0.26 [0.00 to 0.90], showing no statistically significant results, as the log odds ratio contains the zero. The inclusion Bayes Factor (BF) for the effect was 1.225 showing anecdotal supporting evidence for the combination treatment. The inclusion BF for the heterogeneity was 0.979, showing no support for its existence in the analysis and the inclusion BF for the publication bias was 0.622, a lower of 1, indicating evidence of its absence in the analysis. Conclusions. The combination of steroids plus an antiviral agent, is more efficacious than steroid monotherapy in treating Bell’s palsy. This conclusion is supported by frequentist analysis, but not by the Bayesian approach as the Bayesian meta-analysis was inconclusive, suggesting some uncertainty in the effect size but this could be due to priors influence. Further research with advanced syntheses such as network and Bayesian meta-analysis is needed as well as more double-blinded randomized controlled trials.